Awareness, perceptions and adaptation strategies of women in urban fishing village in a climate change environment - a case study in Versova, Mumbai - Debnath, Banti; Krishnan, M.; Ananthan, P.S.; Debnath, Biswajit (Indian Journal of Fisheries, 2016)
This study addressed the awareness, perceptions and adaptation strategies undertaken to cope up with the impact of climate change, by the women in Versova urban fishing village, Mumbai in Maharashtra State. Data collection was carried out with the help of a semi-structured interview schedule, from 90 respondents randomly selected from the village. Respondents were from three different groups belonging to fish marketing, casual labourers and homemakers in fishing households. In Versova fisher families, most of the family members are engaged solely in fisheries related activities and they were able to have a feel of the impact of climate change through various sources like mass media. Loss of shelter and declining income from fisheries complemented by unseasonal heat, decrease in rainfall, decline in fish catch and increase in price of fish for last 5 years were the most important impacts of climate change as perceived by them. All respondents reported lack of alternative livelihood opportunities. The findings of the study could help to develop appropriate strategies and policies to mitigate the impact of climate change to make fisheries more viable and sustainable for both fishers and fishing communities.